Feasibility study of PET/CT for the detection and localization of nervous system damage caused by trimethyltin chloride - Anqing Liu; Qingqiang Tu; Ming Huang (Scientific Reports)
Abstract Trimethyltin chloride (TMT), an organotin compound with potent neurotoxicity, is widely used as a heat stabilizer for plastics. However, the precise pathogenic mechanism of TMT remains incompletely elucidated, and there persists a dearth of sensitive detection methodologies for early diagnosis of TMT. In this study, Sprague-Dawley rats were treated with 10 mg/kg TMT to simulate acute exposure in humans. Micro-positron emission tomography/computed tomography (Micro-PET/CT) and molecular imaging quantitative analysis tools were employed to calculate the uptake rate of 18 F-2-fluoro-D-deoxy-glucose in each functional region of brain tissue. At the same time, the neurobehavioral test and neuropathological results of the experimental rats were compared, aiming to assess the feasibility of PET/CT in the detection and localization of TMT nervous system damage from many aspects. The results showed that TMT decreased glucose uptake in a wide range of brain tissues in rats, and impaired the memory, muscle strength, coordination ability and emotion of rats. Moreover, TMT induced neuronal damage within the cerebral cortex, hippocampal CA1, CA3 and DG regions as well as the cerebellum while also promoting gliosis surrounding the hippocampus. PET/CT imaging results are highly consistent with behavioral and pathological results. In conclusion, TMT induces a widespread reduction in energy metabolism across various brain regions, and PET/CT can serve as a sensitive detection method for TMT-induced encephalopathy.